Strategies for promoting intercultural education in diverse contexts (Revista Electrónica Calidad en la Educación Superior, 2025)
Intercultural education stands as a key element in diverse contexts, fostering peaceful coexistence and mutual respect among cultures. This study uses a mixed quantitative and qualitative design to analyze effective strategies among teachers and students from different institutions. Quantitative results indicate that incorporating diverse content remains the most widely used strategy, while teacher training in interculturality shows low implementation levels. Students value diversity positively, though they identify challenges in inclusion. Chi-square tests reveal a significant relationship between teaching experience and the use of diverse content, but no link with intercultural training. Qualitative analysis highlights barriers such as resistance to change and lack of resources, along with successful strategies like collaborative projects that foster dialogue and reduce prejudice
Keywords: intercultural education; cultural diversity; teacher training; inclusion; collaborative methodologies